Practices and Perceptions of Teacher Educators on Learner Autonomy - Mouni, Ram Bahadur (Journal of Tikapur Multiple Campus, 2024)
This study explores practices and perception of English language teacher educator on learner autonomy. It aimed to identify the ways through which teacher educators practice autonomy in students learning and encourage them be autonomous. Using qualitative narrative inquiry research design, the data were collected through interviews with the five English language teacher educators teaching at undergraduate level, of Far Western University, Nepal. The findings of the study highlight a shared understanding of learner autonomy, emphasizing independent learning, self-direction, and responsibility. Teacher educators stress the pivotal role of instructors in promoting autonomy, advocating for a shift from traditional to student-centered methods. Despite a common understanding, challenges persist, including psychological factors, institutional constraints, and socio-cultural beliefs. The study also suggests the need to address these challenges through targeted strategies for successful promotion of learner autonomy in English language classrooms. Moreover, the study shows that even though it is challenging, teacher educators are making efforts to encourage students be autonomous in providing choices, goal-setting, encouraging self-evaluation, finding out the resources, preparing assignments, having class presentations into classroom practice using different strategies.